CORRELATION BETWEEN CROSS-SECTIONAL AREA of PARASPINAL MUSCLE and PHYSICAL PARAMETERS, OSWESTRY DISABILITY INDEX in PATIENTS WITH LOMBER DISC HERNIATION - Savaş Gürsoy,; Akif Şirikçi,; Ercan Madenci,; Metin Bayram, (Archives of Rheumatology, 2001)
In this study, we aimed to investigate the presence of correlation between cross-sectional area and physical parameters such as, body mass index, age, sex and functional restriction score. Low back pain (LBP) is an important health problem. It is known that the paraspinal muscles were sensitive to different process such as facet degeneration and lomber disc herniation. However, the role of these muscles in LBP and in disc herniation has not been elucidated definitely. Fifty patients with back and leg pain and 25 subjects without back and leg pain were included in this study. While the patients' and controls' tomographic evaluation were performed, total area of psoas major, quadratus lumborum and erector spinea muscles at both side of level L2 were calculated as cm2. Oswestry disability index was calculated for the patients. Patients' and controls' body mass index were also calculated. Patients' cross-sectional area of paraspinal muscles were significantly smaller than that of controls. Cross-sectional area of paraspinal muscle in male patients were significantly greater than that of female patients. There was a significant and negative correlation (r: - 0.367 p: 0.009) between crosssectional area of paraspinal muscles and functional restriction score in the patients group.